Role of nucleoside transporters in transplacental pharmacokinetics of nucleoside reverse transcriptase inhibitors zidovudine and emtricitabine - Karbanova, S; Cerveny, L; Ceckova, M; Ptackova, Z; Jiraskova, L; Greenwood, S; Staud, F (Placenta, 2017)
INTRODUCTION: Zidovudine (AZT) and emtricitabine (FTC) are effective and well tolerated antiretroviral drugs, routinely used in the prevention of perinatal HIV transmission. However, precise mechanism(s) involved in their transfer from mother to fetus are not fully elucidated. Since both drugs are nucleoside analogues, we hypothesized that the mechanisms of their transplacental passage might include equilibrative nucleoside transporters, ENT1 and/or ENT2. METHODS: To address this issue, we performed in vitro accumulation assays in the BeWo placental trophoblast cell line, ex vivo uptake studies in fresh villous fragments isolated from human placenta and in situ dually perfused rat term placenta experiments. RESULTS: Applying this complex array of methods, we did not prove that ENTs play a significant role in transfer of AZT or FTC across the placenta. DISCUSSION: We conclude that the transplacental passage of AZT and FTC is independent of ENTs. Disposition of either compound into the fetal circulation should thus not be affected by ENT-mediated drug-drug interactions or placental expression of the transporters.
Keywords: ENTs; nádorové buněčné linie; těhotenství; emtricitabin; Rats, Wistar; placenta; Cell Line, Tumor; Placenta; Zidovudine; inhibitory reverzní transkriptasy; ekvilibrační proteiny přenášející nukleosidy; ženské pohlaví; zvířata; Humans; Emtricitabine; Pregnancy; Nucleoside transporters; Reverse Transcriptase Inhibitors; potkani Wistar; zidovudin; Female; Equilibrative Nucleoside Transport Proteins; lidé; Animals